Social Responsibility as a Labor Inclusion Strategy for the Development of Public Organization in Ecuador - Rosero-Peña, Lucy (2018)
The objective of the article is to investigate if there is a potential noncompliance and lack of programming in the practice of Social responsibility as a labor inclusion strategy for the development of the Ecuadorian public sector organizations. For this purpose, inquiries were made in two public institutions in order to contrast the empirical application of this obligation, with the practical measures required, both in the short and long term. The results support the proposed hypothesis, proposing a new concept, which, although it does not rule out the routine and experimental philanthropic help action to solve a social problem, but not to foresee it, but it does guarantee the application of a planned methodological process to take successfully carry out an inclusive social responsibility strategy, aimed at generating symbiosis with the different social actors in favor of the common good, facilitating the measurement of the effects and its dissemination through sustainability reports for the knowledge of all stakeholders. Finally, an explanatory model based on international instruments for implementation and reporting on the performance of accountability measures is proposed, focused mainly on the labor insertion of people with special abilities, which contribute to institutional development by integrating them into the various organizational processes, minimizing This way a discriminatory treatment.